1982
DOI: 10.1002/eji.1830120115
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies OKT 11 and OKT 11A have pan‐T reactivity and block sheep erythrocyte “receptors”

Abstract: Monoclonal antibodies OKT11 (gamma 1) and OKT11A (gamma 2) are described and appear to have similar binding specificities. They bind, in immunofluorescence, with greater than 95% of infant thymocytes, staining both cortical and medullary cells, 65-80% of blood lymphocytes and selectively stain the T cell-dependent paracortical areas of tonsil. A small proportion (9-12%) of bone marrow lymphocytes stain, but this population excludes the terminal transferase-positive cells. Both the gamma 1 and gamma 2 antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
1

Year Published

1984
1984
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(65 citation statements)
references
References 22 publications
1
63
0
1
Order By: Relevance
“…In some experiments, PBMC were fractionated into E + and E-cell fractions by rosetting with 2-aminoethylisothiouronium bromide-treated sheep erythrocytes (33) and reconstituted at the indicated E+:E-cell ratios. T cells and NK cells both surface express CD2, which binds to sheep erythrocytes (34)(35)(36)(37), so the E + cell fractions predominantly contained T cells and NK cells.…”
Section: Patients and Controlsmentioning
confidence: 99%
“…In some experiments, PBMC were fractionated into E + and E-cell fractions by rosetting with 2-aminoethylisothiouronium bromide-treated sheep erythrocytes (33) and reconstituted at the indicated E+:E-cell ratios. T cells and NK cells both surface express CD2, which binds to sheep erythrocytes (34)(35)(36)(37), so the E + cell fractions predominantly contained T cells and NK cells.…”
Section: Patients and Controlsmentioning
confidence: 99%
“…The current experiments demonstrated that the expression of the CD2 molecule, i.e., the E-rosette receptor (13,15,17,43), was elevated 10-to 20-fold on human T lymphocytes after activation. The elevation occurred on T cells that were activated either with PHA, which may directly interact with CD2, or with antibody to the CD3-Ti complex (Figs.…”
Section: Discussionmentioning
confidence: 57%
“…The current data are consistent with earlier findings that the E-rosetting properties of T cells are altered by activation in vitro (10,33,34) andor by certain disease conditions (16) is synthesized in increased amounts on activated T cells, and that this increased amount correlated with the formation of stable E-rosettes. In contrast to other activation antigens that are not detectable on resting T cells, e.g., the TCGF receptor (7,191, the transferrin receptor (7,12,40), or the molecule recognized by the 4F2 antibody (7,11), CD2 is already present on resting cells in readily detectable amounts (13,15,17,43). In spite of this difference between CD2 and Tac expression on freshly isolated T cells, the initial increase in CD2 expression during PHA-stimulated T cell activation occurred at the same time and on the same cells that initially began to express TCGF receptors (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations